Magnetism and the phase diagram of MnSb2O6 - Koo, Changhyun; Werner, Johannes; Tzschoppe, Michael; Klingeler, Rüdiger (Physical review, 2018)
Static and dynamic magnetic properties of P¯31m-phase MnSb2O6 have been studied by means of muon-spin relaxation (μSR), high-frequency electron-spin resonance (HF-ESR), specific heat, and magnetization studies in magnetic fields up to 25 T. The data imply onset of long-range antiferromagnetic order at TN = 8 K and a spin-flop-like transition at BSF ≈ 0.7-1 T. Below TN, muon asymmetry exhibits well-defined oscillations indicating a narrow distribution of the local fields. A competing antiferromagnetic phase appearing below TN2 = 5.3 K is evidenced by a step in the magnetization and a slight kink of the relaxation rate. Above TN, both μSR and HF-ESR data suggest short-range spin order. HF-ESR data show that local magnetic fields persist up to at least 12TN≈100 K. Analysis of the antiferromagnetic resonance modes and the thermodynamic spin-flop field suggest zero-field splitting of Δ≈18 GHz which implies small but finite magnetic anisotropy.
Die Ziffern der chemischen Formel im Titel erscheinen tiefgestellt
Gesehen am 21.01.2020